Geofiltration studies of clay at the future radioactive waste repository for Ignalina nuclear power plant - Klizas, Petras (Journal of Environmental Engineering and Landscape Management, 2014)
Clay geofiltration studies became important in Lithuania when the clays began to be used as geofiltration barriers for waste disposal sites/repositories. The clay is planned to be used also in construction of the future radioactive waste repository for the Ignalina Nuclear Power Plant. The results of investigation on Stabatiškė subformation till clay occurring at the base of the repository are given in the paper. The investigation has been performed with the purpose to determine potential dependence of clay filtration coefficient values on the number of freeze-thaw cycles and duration of filtration. The filtration coefficient for the repository till clay has been found to be greatly varying at the start of the filtration and during the experiment that lasted several days. This confirms that, during the filtration, structural changeover of clay-forming aggregates takes place with pore space volumes changing and affecting the filtration coefficient values. The filtration parameters are even more affected by freeze-thaw cycles and their number. When the clay thaw is finished the colmatation of fissure system is very slow and incomplete.First published online: 15 May 2014